INOVASI KETERAMPILAN KULINER PENGOLAHAN NANGKA MUDA BERSAMA WARGA DAN IBU PKK DESA MARGA MULYA - Selawat Setiawan; Hutami Nur Aini; Aisyah Nur Rahmah; Andriany Sudirman; Muchrifah Muchrifah; Abdul Kadir Jailani; Eka Widyanti (P3M STAI Sangatta, 2026)
The suboptimal utilization of local natural resources is one of the problems faced by rural communities, including in Marga Mulya Village, which has an abundant supply of young jackfruit. Until now, young jackfruit has only been used as a simple vegetable with relatively low economic value. This Community Service Activity (PKM) aims to increase the knowledge and skills of the community through innovations in processing young jackfruit into jackfruit floss and megono as value-added food products. The activity was carried out using a participatory approach based on socialization and training, which was held on November 26, 2025, at the PKK Building in Marga Mulya Village, involving the women of the Marga Mulya Village PKK and the Kombeng Subdistrict PKK. The results of the activity showed that the innovation in processing young jackfruit was able to produce jackfruit floss and megono with good taste, texture, and sales value potential. The evaluation of the activity showed that 90% of participants understood the process of making jackfruit floss and 88% of participants understood the process of making megono, and 85% of participants were able to practice it independently. This activity had a positive impact in the form of increased community capacity, growing awareness of the utilization of local potential, and the emergence of home-based business opportunities based on local food processing.